The Forgotten Effects on Fishing Cooperatives in Altata Bay - Soto Ruiz, Gerardo Eloy; Valenzuela Flores, Victoriana; Gil-Lafuente, Anna María; Sanchez Valenzuela, Kenia (Unidad Editorial UPTC, 2022)
in the face of the crisis of the prevailing economic model in the world, Elinor Ostrom's thesis based on the self-organization of people in the exploitation of common-use resources, with proposals to mitigate the deterioration of nature and its own pollution, is gaining strength. The article focuses on the study of seven fishing cooperatives, one located in the municipality of Culiacán and six in the municipality of Navolato in the State of Sinaloa. A model based on the principles of the theory of fuzzy subsets, called the forgotten effects, is used to determine the effects that are not easily observable. The study found causal relationships that were not originally considered by the experts. It is concluded that the use of this methodology is appropriate in the application of strategies that facilitate the implementation of a model of organizational culture that encourages participation and gives responsibility to the people grouped in organizations that promote a social economy in Mexico. JEL Codes: D8, P13, Q22 Received: 15/07/2021.  Accepted: 04/04/2022.  Published: 01/06/2022.